Determination of Foundation Settlements - Tereffe, Getaneh (Zede Journal of Ethiopian Engineers and Architects, 2023)
This paper deals with two major problems: Determination of the thickness of the soil to be considered as compressed by the given load (z') using computer or grapho-analytical solution. Determination of foundation settlements using simple formula without determining natural and additional pressures for each elemental soil layer. When computing foundation settlement a single influence factor is used for the affected soil thickness. The influence factor is a function of foundation dimension ratio and accounts the thickness of the compressible layer (z'). The factor is tabulated for practical use. In addition, cases for a uniform and stratified soil layers are considered when determining foundation settlement. Illustrative examples are given as comparison between the 'Summation Method' and the Proposed Formulae. Finally, the proposed method is believed to be rapid, practical and more reliable since the cumulative errors of pressure increment by the 'Summation Method' is eliminated with.